2007
DOI: 10.1002/hep.21917
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated interferon alpha-2b plus ribavirin in patients with genotype 4 chronic hepatitis C: The role of rapid and early virologic response

Abstract: In patients chronically infected with hepatitis C virus (HCV) genotype 4, the optimum duration of therapy and the predictors of sustained virologic response (SVR) have not been adequately determined. In this study, 358 patients with chronic hepatitis C genotype 4 were randomly assigned to pegylated interferon (PEG-IFN) alpha-2b (1.5 g/kg/week) plus oral ribavirin (10.6 mg/kg/day) for a fixed duration of 48 weeks (control group, n ‫؍‬ 50) or for a variable duration (n ‫؍‬ 318). In the variable-duration group, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
2
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 29 publications
9
118
2
6
Order By: Relevance
“…The presence of such a cheaper yet effective alternative will immensely aid the national efforts to eradicate HCV. Interim responses also compared similarly, yet our RVR rate was unexpectedly high (54%) in comparison to previous reports of only 16%-45% with 40 kDa interferon (Kamal and others 2007;Ferenci and others 2008). We postulated that this might be due to the strict measures we took to ensure compliance in the early weeks of treatment, but this argument, however, fails to explain why the high RVR did not translate to higher ETR and SVR rates.…”
Section: Discussioncontrasting
confidence: 73%
“…The presence of such a cheaper yet effective alternative will immensely aid the national efforts to eradicate HCV. Interim responses also compared similarly, yet our RVR rate was unexpectedly high (54%) in comparison to previous reports of only 16%-45% with 40 kDa interferon (Kamal and others 2007;Ferenci and others 2008). We postulated that this might be due to the strict measures we took to ensure compliance in the early weeks of treatment, but this argument, however, fails to explain why the high RVR did not translate to higher ETR and SVR rates.…”
Section: Discussioncontrasting
confidence: 73%
“…In the current study, all genotype 1 patients (n = 7) who achieved RVR also attained SVR; while a study reported a SVR rate of 86.8% in patients with RVR [15] . In genotype 4 patients, 80% with RVR attained SVR, whereas the published study reported 86% [23] . Similarly, among the genotype 3 patients who had RVR, 83.3% attained SVR, which is similar (83.7%) to that reported in the literature [24] .…”
Section: Discussionmentioning
confidence: 76%
“…Although sustained viral response after treatment with interferon alfa monotherapy was 10% -15%, the addition of ribavirin significantly improved the response rated to 30% -40% [6]. Most recently, the use of pegylated interferon has further improved response rate, and more than half of the treated patients can expert to have a sustained response with combination therapy using peginterferon and ribavirin [7].…”
Section: Interferonmentioning
confidence: 99%